Monitoring Knowledge, Attitudes, and Practices on Restraint Use in Adult and Pediatric Intensive Care Units: The Multicenter Development and Validation of the CON-Ti-IT Questionnaire. - Dittura, Loredana; Schreiber, Silvana; Guidi, Valentina; Giangreco, Manuela; Zamagni, Giulia; Venier, Erica; Di Meola, Raffaella; Balestreri, Elisabetta; Toso, Giorgia; Sartorato, Patrizia; Bertocchi, Luca; Buchini, Sara; et al. (Nursing Reports, 2026)
Background/Objectives: The use of physical restraints in adult and pediatric intensive care units (ICUs) is common yet controversial. While restraints are intended to prevent treatment interference or self-harm, they pose significant physical, psychological, and ethical risks. Nurses in intensive care units play a key role in decisions about restraint application, but there is a global lack of validated tools to assess their knowledge, attitudes, and practices, particularly in non-English-speaking contexts. Aim of this study was to develop and validate a questionnaire for assessing knowledge, attitudes, and practices (KAP) of ICU nurses regarding restraint use in adult and pediatric settings. Materials and Methods: A multi-method psychometric validation study was conducted across both adult and pediatric ICU settings at two hospitals in northern Italy. Questionnaire development included literature review, expert consultation, and iterative content and face validity assessments. Reliability was tested using test–retest methods, and construct validity was explored through exploratory factor analysis. The study followed COSMIN guidelines. Results: The final CON-Ti-IT questionnaire comprised 29 items across three subscales: Practices, Attitudes, and Knowledge. It demonstrated strong content validity (CVI = 0.96) and good internal consistency for the Practices subscale (Cronbach's α = 0.89). Internal consistency for the Attitudes (α = 0.51) and Knowledge (α = 0.47) subscales was lower, reflecting the broader conceptual variability of these domains. Exploratory factor analysis confirmed the structural validity of the tool and led to the removal of three items with low factor loadings. Conclusions: This study presents the first validated tool specifically designed to evaluate ICU nurses' KAP on restraint in adult and pediatric settings. While developed and validated in Italy, it could undergo cross-cultural adaptation and translation for use in other languages and healthcare systems. Its strong psychometric properties support its application in future research, and the data collected through its use can serve both to improve patient care and to provide a foundation for targeted educational initiatives.